2019
DOI: 10.18026/cbayarsos.475162
|View full text |Cite
|
Sign up to set email alerts
|

Fen Bi̇lgi̇si̇ Öğretmen Adaylarinin Fi̇zi̇k, Ki̇mya Ve Bi̇yoloji̇ Deneyleri̇ne Yöneli̇k Algilarinin Metaforlar Araciliği İle İncelenmesi̇

Abstract: Bu çalışmada fen bilgisi öğretmen adaylarının fizik, kimya ve biyoloji deneylerine yönelik algılarının metaforlar aracılığı ile incelenmesi amaçlanmıştır. Çalışmaya fen bilgisi eğitimi anabilim dalı 3. sınıfta öğrenim görmekte olan 68 öğretmen adayı katılmıştır. Bu nitel araştırmada fenomenoloji deseni kullanılmıştır. Öğretmen adaylarından "Fizik deneyleri …………… gibidir. Çünkü ……………", "Kimya deneyleri …………… gibidir. Çünkü ……………", "Biyoloji deneyleri…………… gibidir. Çünkü ……………" cümlelerini tamamlamaları istenmiş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
4
0
4
Order By: Relevance
“…In recent years, metaphors and metaphorical perceptions have also been determined by using other concepts related to the concept of "physics". As an example of this; "physics and physics problems" (e.g., Toksoy and Akdeniz 2020), and "physics experiments" (e.g., Harman and Şeker, 2019). Having look at all the studies mentioned above, it was seen that metaphors about "physics teacher" could not been adequately researched.…”
Section: Extended Abstractmentioning
confidence: 99%
“…In recent years, metaphors and metaphorical perceptions have also been determined by using other concepts related to the concept of "physics". As an example of this; "physics and physics problems" (e.g., Toksoy and Akdeniz 2020), and "physics experiments" (e.g., Harman and Şeker, 2019). Having look at all the studies mentioned above, it was seen that metaphors about "physics teacher" could not been adequately researched.…”
Section: Extended Abstractmentioning
confidence: 99%
“…Özgün ve diğ., (2018) öğretmen adayları üzerinde yaptıkları araştırma sonuçlarına göre bilimsel araştırmanın "çaba-emek ve araştırmaya bağlı bir yapı", bilim insanını ise "araştıran-çabalayan-çalışkan bir kişi olarak algılandığını tespit etmişlerdir. Alan yazında farklı alanlardaki öğretmen adaylarıyla yapılan araştırmaların sonuçlarına göre öğretmen adaylarının bilimsel araştırmayı sonuca ulaşma şekli ve sonuca ulaşma sürecindeki işlemler olarak algıladıkları tespit edilmiştir (Akgün, 2012;Harman & Şeker, 2019;Küçükoğlu & diğ., 2013;Taşdemir & Taşdemir, 2016 (Akgün, 2012;Çepni & diğ., 2003;Harman & Şeker, 2019;Saban, 2007).…”
Section: öğRetmen Adaylarının Bilimsel Araştırmaya Yönelik Algılarıunclassified
“…In particular, during the undergraduate education period, where professional knowledge is gained, the education received by teacher candidates stands out in terms of scientific research and scientist perceptions. In the literature, there are studies conducted to determine the metaphorical perceptions of teacher candidates on scientific research and scientists (Bartan, 2019;Çetin et al, 2019;Harman & Şeker, 2019;Kösem, 2017;Özgün et al, 2018;Taşdemir & Taşdemir, 2016). Few studies have been found to determine the perceptions of social studies teacher candidates on scientific research (Çal & Demirkaya, 2018;Ürey et al, 2017).…”
Section: Extended Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…about even the most basic astronomical issues (Bostan, 2008). The fact that many of the astronomical concepts such as stars are complex/difficult to learn or abstract, has led to the use of different methods to concretize these concepts (Harman, 2012). Computer-assisted teaching, augmented reality, models are some of the methods that can be used.…”
Section: Introductionmentioning
confidence: 99%